EFFECTIVENESS AND SAFETY OF INFLIXIMAB IN PATIENTS WITH EARLY JUVENILE RHEUMATOID ARTHRITIS - E.I. Alexeeva; T.V. Sleptsova; S.I. Valieva; T.M. Bzarova; R.V. Denisova; A.O. Lisitsin; E.Yu. Gudkova; A.M. Chomakhidze; K.B. Isaeva; A.A. Grigor'eva; O.L. Lomakina ("Paediatrician" Publishers LLC, 2009)
The article presents the results of a study of effectiveness and safety of infliximab - monoclonal antibodies to tumor necrotizing factor (TNF) _ in treatment of 47 patients in age 11 months - 16 years old with early pauciarticular and polyarticular types of juvenile rheumatoid arthritis. The duration of observation was from 3 months to 1 year. Infliximab was administrated intravenously according to scheme: infusions on 0, 2, 6 and further every 8 weeks. Single dose of infliximab in patients with polyarticular type of juvenile arthritis was 6.75 ± 2.16 mg/kg, and in patients with pauciarticular type - 7.35 ± 2.09 mg/kg of body weight. Treatment with anti-TNF medication during 54 weeks resulted in development of clinical remission, decrease and normalization of laboratory rates of disease's activity, complete restoration of joints' function, and increase of quality of life in 83% of patients. The secondary absence of effectiveness developed in 3 patients, and they were excluded from the study. The tolerability to the medication was satisfactory: there was no any unfavorable event needed abolition of treatment during all period of observation. Key words: children, early juvenile rheumatoid arthritis, treatment, infliximab. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):42-50)